Impact of obesity on quality of life: Case of the Rabat-Salé-Kénitra Region, Morocco (Bangladesh Journal of Medical Science, 2025)
Aims This study aims to investigate the impact of obesity on quality of life, focusing on physical activity limitations among adults in the Rabat-Salé-Kénitra region of Morocco. Materials and Methods A cross-sectional study was conducted between January 2021 and August 2022, involving a random sample of 134 individuals aged 18 to 59 years. Inclusion criteria excluded chronic conditions likely to affect weight or physical activity. Data were collected using sociodemographic an anthropometric questionnaires, alongside the MOS SF-36 scale to assess healthrelated quality of life. Statistical analyses, including chi-square tests and Z-scores, were used to evaluate associations between key variables. Results and Discussion The sample predominantly consisted of women (62.7%), with a mean age of 39.34 ± 1.08 years. Over 72% of participants were classified as overweight or obese, and 17.6% experienced severe physical activity limitations. Significant associations were observed between physical activity limitations and factors such as BMI, urban residence, and educational level. The study also highlighted a high prevalence of comorbidities, including diabetes, orthopedic conditions, and psychiatric disorders, further emphasizing the detrimental impact of excess weight on quality of life. These findings align with global research while underscoring regional specificities. Conclusion Obesity significantly impairs quality of life through its impact on physical activity limitations and associated comorbidities. These results highlight the urgent need for public health interventions promoting physical activity and addressing the socio-economic and cultural determinants of obesity.Bangladesh Journal of Medical Science Vol. 24 No. 02 April’25 Page : 670-678